"It's not Just Camp!": Understanding the Meaning of Children's Cancer Camps for Children and Families. (January 2016) - Laing, Catherine M.; Moules, Nancy J.
The purpose of this philosophical hermeneutic inquiry was to understand the meaning of children's cancer camps for the child with cancer and the family. Six childhood cancer families and 5 cancer camp counselors were interviewed, in order to bring understanding to this topic. Findings from this research revealed that camp means different things for different families, and that much is at play in the cancer camp experience: the healing and developmental power of play, finding acceptance and fit, grief as something to live with versus "get over, " storytelling as a means of reshaping and understanding traumatic experiences, and the solidarity of the community as one that creates intense, healing bonds. Children's cancer camps, we conclude, should be considered a necessity, versus a luxury, and could even be thought of as a psychosocial intervention for some children and families. Barriers such as structure of funding and access to resources are present and likely due to the separateness of camps from hospital programs.